2013
DOI: 10.1002/esp.3384
|View full text |Cite
|
Sign up to set email alerts
|

Initial hydro‐geomorphic development and rill network evolution in an artificial catchment

Abstract: The formation of erosion rills and gullies is a critical step in land surface development, but possibilities to study initial unaffected surface development under natural conditions and with well‐defined initial and boundary conditions are rare. The objective of this study was to characterize rill network development from ’point zero’ in the artificially‐created catchment ‘Hühnerwasser’. To ensure unaffected development, the study was largely restricted to the analysis of remotely‐sensed data. We analyzed a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 99 publications
2
31
0
Order By: Relevance
“…Erosion and deposition processes were clearly evident in the Chicken Creek catchment during the first years without plant cover. Substantial surface changes resulted from rill erosion, as aerial photographs (rill network) and a comparison of photogrammetry-based digital elevation models showed (Schneider et al, 2013). Interrill erosion did not lead to surface changes larger than about 20 cm during the first 5 years.…”
Section: Soil Samplingmentioning
confidence: 93%
“…Erosion and deposition processes were clearly evident in the Chicken Creek catchment during the first years without plant cover. Substantial surface changes resulted from rill erosion, as aerial photographs (rill network) and a comparison of photogrammetry-based digital elevation models showed (Schneider et al, 2013). Interrill erosion did not lead to surface changes larger than about 20 cm during the first 5 years.…”
Section: Soil Samplingmentioning
confidence: 93%
“…-Modern techniques such as laser scan measurements should offer the potential to get observational data on soil dislocation by erosional events (Schneider et al 2013, Deumlich et al 2014 …”
Section: Discussionmentioning
confidence: 99%
“…The erosion and deposition processes during the initial development period strongly modified not only the surface topography (Schneider et al, 2013) but also the spatial distribution of sediment composition (Fig. 9).…”
Section: Resultsmentioning
confidence: 99%
“…While for hydrologic catchments with well‐established forest or well‐managed agricultural ecosystems the spatial structures may possibly be assumed to remain relatively constant, this cannot be assumed for systems that are in an initial stage of development (Schaaf et al, 2011). Characteristic changes in the spatial structures due to erosion and sedimentation or surface crust development (e.g., Belnap et al, 2001; Fischer et al, 2010a, 2010b; Spröte et al, 2010; Schneider et al, 2013) that could be observed during the initial development stages could in turn affect flow and transport in the catchment. Such feedback relations between overland flow, erosion, and rill network development were highly complex (e.g., Brunton and Bryan, 2000).…”
mentioning
confidence: 99%